2022
DOI: 10.1177/14771535211044665
|View full text |Cite
|
Sign up to set email alerts
|

Investigating mean room surface exitance values for office lighting

Abstract: Mean room surface exitance (MRSE) is a metric proposed to assess lighting quantity within a new design methodology focused on ambient and target illumination. This research builds upon findings from previous research examining the suitability of MRSE as a metric for assessing ambient illumination brightness levels and illumination adequacy for offices. An experiment was conducted to investigate a finding from previous studies that a linear relationship existed between perceived adequacy of illumination (PAI) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…Duff et al 11,12 have reported a significant linear relationship between spatial brightness and MRSE over a range of 25–100 lm/m 2 , while a recent study by Durante and Kelly 13 over an extended range of 25–1400 lm/m 2 and has determined the exponential relationship shown in equation (1).…”
Section: Human Response Metricsmentioning
confidence: 95%
“…Duff et al 11,12 have reported a significant linear relationship between spatial brightness and MRSE over a range of 25–100 lm/m 2 , while a recent study by Durante and Kelly 13 over an extended range of 25–1400 lm/m 2 and has determined the exponential relationship shown in equation (1).…”
Section: Human Response Metricsmentioning
confidence: 95%